Elitist or egalitarian spelling? The Romantic dilemmas - Stęplewski, Artur (Poznańskie Studia Slawistyczne, 2011)
Spelling is not just a problem for students, it is also a serious political issue. This especially concerns the time when the standard literary languages are formed. The problem of spelling also appears when there are important social changes, revolutions, wars, and a change of political system. One introduces spelling democratization for all members of the community or, conversely, spelling becomes an elite, intended for a narrow audience. The article presents the problem of spelling in Poland and Czech (Bohemia) in the 19th century and nowadays.